Community Garden Project, Mildred Hall School Yellowknife ... - Campbell, Sandy (University of Alberta Library, 2015)
This garden project at Mildred Hall School in Yellowknife is a collaboration between students and elders. Raised beds are a common garden format in Yellowknife because of the rocky nature of the landscape and the general lack of good topsoil. These beds contain common garden plants such as potatoes, beets, lettuce and peas. Throughout the North there is a new emphasis on food sustainability. Helping students learn to grow food is a part of that movement. ...